Assessment for late developmental hip dysplasia in a cohort of infants with risk factors and normal hip ultrasound - Morello, Rosa; Bocchi, Beatrice; Mariani, Francesco; Bononi, Alice; Giuli, Cristina; Bonfiglio, Nadia; Valentini, Piero; Lazzareschi, Ilaria; Rendeli, Claudia; Palmacci, Osvaldo; Buonsenso, Danilo (Frontiers in Pediatrics, 2023)
Background: Developmental dysplasia of the hip (DDH) is a known orthopedic pathology of newborns that if not diagnosed and treated, can lead to debilitating long-term consequences. Ultrasound has proven to be an effective method for early diagnosis, especially in patients with risk factors. Recently, reports of late DDH in populations at risk (breech presentation) and after negative ultrasound examination have emerged in the literature. Aim: the objective of the study was to assess the possible appearance of late DDH in Italian children with risk factors but negative ultrasound screening. Materials and methods: The authors selected patients with risk factors for DDH and negative hip ultrasound, analyzing retrospectively the medical records of children referred to the Hip Ultrasound Clinic (Rome, Italy) from January 2018 to November 2021. To identify possible cases of late DDH, from February 2022 to July 2022 all patients who met the inclusion criteria were submitted to orthopedic follow-up clinical evaluation. In the case of pathological objective examination, radiography was performed. Results: Fifty-five patients (52.7% female, 52.7% with breech presentation, 41. 8% with a positive family history) met the inclusion criteria. The median age of gait onset was 13 months. The median age of orthopedic follow-up examination was 45 months. Only three patients (5.5%) had a pathological examination, but none x-rays was pathological. Conclusion: our study has not documented cases of late DDH. Considering the small study population and the only clinical follow-up, further studies are needed to clarify the possible late development of this condition.